Intraspecific variation of the octotaxic system in Protoribates paracapucinus (Acari, Oribatida, Haplozetidae), with systematic and taxonomic considerations - Weigmann, Gerd; Ermilov, Sergey G. (Zootaxa, 2016)
The octotaxic system of notogaster in poronotic oribatid mites (Acari, Oribatida) usually is represented by two types, either porose areas or saccules. These dermal gland structures are observed as constant for each species (except sexual dimorphism; see below), therefore their type often is used as key character, and in consequence of this, it is used in taxonomy and systematics as diagnostic character for different taxa levels from species to family (Subías 2004, online version 2015; Weigmann 2006; Norton & Behan-Pelletier 2009; Bayartogtokh 2010). However, there are exceptions: for Drymobates silvicola Grandjean, 1930 (Drymobatidae) and Galumna (Atypicogalumna) corpuzrarosae Ermilov, Sandmann, Klarner, Widyastuti & Scheu, 2015 (Galumnidae), a composite octotaxic system is known, including side by side porose areas and saccules in every specimen (Grandjean 1930; Ermilov et al. 2015). Behan-Pelletier (2015) reports several cases of sexual dimorphism of the octotaxic system in Poronota, all with different appearance of porose areas. But for the licneremaeoid Glanderemaeus hammerae Balogh & Csiszár, 1963 (whose familial placement is unclear) a unique sexual dimorphism in octotaxic system is described—males with saccules, females with porose areas (see also Norton et al. 1997).